Optical and structural properties of PbS:Bi^3+ nanocrystals - Gutiérrez Pérez, R.; Portillo Moreno, O.; Chaltel Lima, L.; Chávez Portillo, M.; Palomino Merino, R.; Zamora Totozintle, M. (Revista Mexicana de Física, 2015)
We report here the growth of nanocrystalline PbS thin films by chemical bath and the effects of doping on the structural and electronics properties as a function of Bi^3+ concentration. Doping of such PbS films with Bi^3+ produces considerable optical and structural changes that have an effect on the material properties. The morphological changes of the layers were followed by Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM). X-ray diffraction (XRD) spectra show growth of the zinc blende phase. The grain size for the undoped samples was found to be 32 nm, whereas that for the doped samples was 25-15 nm, thus confirming AFM and SEM results. A conspicuous shift for the forbidden band gap energy was observed by optical absorption from 1.2 eV for the undoped samples to a 1.7-2.0 eV range for the doped films.